GENDER DAN KESALEHAN POPULAR ARTIS BERKERUDUNG (Studi Atas Buku â€œAku dan Hijabku, Hijab is not Just a Styleâ€) - M. Endy Saputro (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2017)
The openness of a religion towards new insights leads tochanges of symbolic order as well as the characteristics and performanceof the religion. Nowadays, many people assume that spirituality can beachieved in the mass consumption for symbols, icons and cult objectsso that a consumer culture makes up the opportunity to meet the desireand evoke the human subconscious. One of the cultures is the changesof Muslims fashion in Indonesia. Some artists start to wear jilbab and itbecomes a trend among ordinary people. As we know, jilbab is obligatoryto some female Muslims, but nowadays it is likely a kind of trend in fashion.In fact, jilbab itself shows the identity of female Muslims. When a femaleMuslim has decided to wear jilbab, it is sure that she has got the hidayah(inspiration) to make herself closer to God. Among the motivations of artiststo wear jilbab is the fulfillment of their spiritual need and other factors arealso possible.